PEMBUATAN SPEED TRAP SEBAGAI ALAT PENGENDALI PENGGUNA JALAN - Maureen, Yoleen (JURNAL MEDIA TEKNIK, 2011)
ABSTRACTIn an effort to promote development and national integrity as part of efforts to promote the general welfare, Traffic and Road Transportation is having a very strategic role. In addition, as part of the national transportation system isnecessary to develop their potential, to realize the security, safety, order and smoothness. Accordingly, the Acts No. 22 has been set up everything on Road Traffic and Transportation. As stipulated in article 25 paragraph (1), that any road that is used for public traffic shall be equipped with road equipment. One is the control devices and road user safety. In this case in Indonesia commonly known as speed bumps or speed trap / traffic bump. In Indonesia provisionsregulating the speed trap are the Minister of Communications Decree No. 3 of 1994 on Controls and Road User Safety. But the reality is often encountered in the cities of our country, there are very many people who do not realize the importance of rules that must be adhered to for comfort and common interests. The existence of the technical provisions of the Instrument Control and Road User Safety has been made should more attention again to the community and theorganizers of the road.Keywords :`Nasionl Transportation Systems, Controls and safety of road users, Speed Limiting Device, Speed Trap